Skeletal benefits of pre-menarcheal gymnastics are retained after activity cessation - Scerpella, T.; Dowthwaite, J. N.; Gero, N.; Kanaley, J.; Ploutz-Snyder, R. J. (Pediatric Exercise Science, 2010)
Mechanical loading during childhood and adolescence may yield skeletal benefits that persist beyond activity cessation and menarche. At 1 year pre- and 2 years post-menarche, nondominant forearm areal bone mineral density (aBMD), bone mineral content (BMC) and projected area (area) were compared in gymnasts (n = 9), ex-gymnasts (n = 8) and nongymnasts (n = 13). At both observations, gymnasts and ex-gymnasts had higher forearm aBMD, BMC and area than nongymnasts. Gymnasts had higher postmenarcheal means than ex-gymnasts for all three parameters. Childhood mechanical loading yields skeletal advantages that persist at least 24 months after loading cessation and menarche. Continued postmenarcheal loading yields additional benefit.